Who Gains from Services FDI—Host or Home Economies? An Analysis of Disaggregated Services FDI Inflows and Outflows of 24 European Economies - Doytch, Nadia (Archīum Ateneo, 2021)
This study focuses on a sample of 24 European economies to examine the spillovers from disaggregated services foreign direct investment (FDI) on economic growth. We study the impact of 20 disaggregated services FDI inflows and outflows, respectively, on their host and home country services sector and overall growth. We find that both financial services and business services FDI are beneficial for growth in both host and home countries. Financial services FDI works though financial holding companies and home countries benefit especially from investment in foreign banks, which provides access to credit. Business services FDI works though management holding companies and home countries benefit, especially from investment in computer activities, which provides access to specialised human capital and high-value knowledge assets. The positive spillovers to home countries provide evidence for arguing against protectionism. JEL Codes: F2, F21, F43